Development and Validation of Loperamide Hydrochloride Tablet Analysis Method with Absorbance and Area under Curve Methods Spectrophotometrically - Harrizul Rivai; Renny Puspita; Sesry Misfadhila (Fakultas Farmasi Universitas Andalas, 2018)
Development and validation of loperamide hydrochloride tablet method of analysis with absorbance method and area under the curve method have been done. This study used methanol and hydrochloric acid 0.1 N (9: 1) as the best solvent with maximum absorption at wavelength 259.00 nm. Linearity of loperamide hydrochloride was obtained in the concentration range 200-600 ppm with correlation coefficient value with absorbance method and the areas under the curve method were 0.9998 and 0.9865, respectively. The results showed that the levels of loperamide hydrochloride in generic tablets obtained by absorbance method and the area under the curve method were 105.71% and 96.20%, respectively. The results of determination of loperamide levels in tablets of trademark obtained by absorbance method and the area under the curve method were 102.85% and 98.57%, respectively. The level of both samples met the requirements of Pharmacopoeia Indonesia edition V that is 90% -110%.